2019
DOI: 10.7326/m18-1570
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation and Survival Among Patients With Lupus Nephritis

Abstract: Background: Patients with end-stage renal disease (ESRD) due to lupus nephritis (LN) have high rates of premature death. Objective: To assess the potential effect on survival of renal transplant among patients with ESRD due to LN (LN-ESRD) in the United States. Design: Nationwide cohort study. Setting: United States Renal Data System, the national database of nearly all patients with ESRD. Participants: Patients with incident LN-ESRD who were waitlisted for a renal transplant. Measurements: First renal transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…HR: 0.30, 95% CI 0.27 to 0.33), along with reductions in cause-specific mortality (CVD, infections, sepsis, etc). 112…”
Section: Resultsmentioning
confidence: 99%
“…HR: 0.30, 95% CI 0.27 to 0.33), along with reductions in cause-specific mortality (CVD, infections, sepsis, etc). 112…”
Section: Resultsmentioning
confidence: 99%
“…107 108 By contrast, kidney transplantation is associated with higher 10-year patient survival rates 109 110 ; data from the United States Renal Data System showed 70% reduced mortality among patients with LN-ESKD who underwent transplantation as compared with non-transplanted counterparts. 111 The updated statement now emphasises that 'transplantation may be preferred over other kidney replacement options and should be considered when extra-renal lupus is clinically (and ideally, serologically) inactive for at least 6 months'. Currently, only a small fraction of patients undergo pre-emptive transplantation, although this strategy has the most favourable outcome ( survival rates 94%,vs 76% and 42%, for peritoneal dialysis and haemodialysis, respectively).…”
Section: Management Of Eskd In Lnmentioning
confidence: 99%
“…Nationwide cohort study in US confirmed that renal transplantation was associated with a survival benefit in LN-ESRD, primarily due to reduced deaths from cardiovascular disease and infection. [ 23 ] One of the most advanced researches of LN in 2019 was the discovery of immune cell landscape in kidney. [ 24 ] By using single-cell RNA sequencing, scientists mapped 21 immune cell clusters in LN kidney, including B cells, T cells, natural killer cells, myeloid cells, and epithelial cells.…”
Section: Advances On Clinical Manifestations In Slementioning
confidence: 99%